The 4.0 Skills Gap of Workers in Vietnam's Industrial Parks in the Context of the Fourth Industrial Revolution: Some Initial Thoughts - Thi Quynh Anh, Nguyen; Thu Trang, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 40 No 2DO - 10.25073/2588-1116/vnupam.4457, 2024)
The Fourth Industrial Revolution with its modern digital technologies will completely transform labor methods and human resource management. The Fourth Industrial Revolution also exacerbates the skills gap among workers. The imbalance in skills manifests as a shortage of necessary skills to meet current labor market demands or a surplus when certain skills are easily found in the labor market compared to the demand from businesses/employers. In industrial zones, when businesses implement semi-automation or automation in production, workers without the "appropriate" skills for new positions or changes in production will face job loss and unemployment. This article focuses on identifying the issue of the skills gap within the context of the Fourth Industrial Revolution and the impacts of this issue on related entities such as businesses, localities, training institutions, and professional associations.